Cascade Biotransformation to Access 3‐Methylpiperidine in Whole Cells. Issue 23 (10th July 2019) - Borlinghaus, Niels; Weinmann, Leonie; Krimpzer, Florian; Scheller, Philipp N.; Al‐Shameri, Ammar; Lauterbach, Lars; Coquel, Anne‐Sophie; Lattemann, Claus; Hauer, Bernhard; Nestl, Bettina M.
Abstract: Synthesis of 3‐methylpiperidine from 1, 5‐diamino‐2‐methylpentane in preparative scale is reported by using recombinant Escherichia coli cells expressing a variant of the diamine oxidase from Rhodococcus erythroprolis and an imine reductase from Streptosporangium roseum . Optimization of process parameters for cultivation and bioconversion led to substantial improvements in the initial laboratory procedure. The transformation of the methyl‐substituted diamine substrate to the N ‐heterocyclic product was successfully scaled‐up from shake‐flask to a 20 L bioreactor with increased substrate concentrations. Remarkably, we obtained 67 % of 3‐methylpiperidine product from 140 g substrate within 52 h. Abstract : Scaling Up ! The coupling of engineered putrescine oxidase and imine reductase realizes the preparation of piperidine heterocycles. Particularly, the production of 3‐methylpiperidine at 20 L scale was demonstrated using an E. coli whole‐cell system.